2005
DOI: 10.1111/j.1445-2197.2005.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous splanchnic nerve radiofrequency ablation for chronic abdominal pain

Abstract: Although preliminary data regarding RFA ablation of splanchnic nerves are encouraging, further trials are also needed comparing percutaneous splanchnic nerve ablation with opioid analgesia and coeliac plexus blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 35 publications
(25 reference statements)
2
46
0
1
Order By: Relevance
“…Raj et al [ 21 ] reported that up to 40% of patients had excellent pain relief after a thoracic splanchnic nerve block, with only 15% of patients reporting poor results in a series of 107 patients with abdominal pain [ 21 ] . One study consisting of eight patients with chronic pancreatitis and two patients with chronic abdominal pain of an unknown etiology found that splanchnic radio-frequency ablation resulted in decreased pain scores, opiate usage, and hospital admissions for pain control [ 20 ] . Garcea et al [ 20 ] also found patients to have improvement in their level of anxiety, daily activity, mood, and overall perception of health.…”
Section: Splanchnicmentioning
confidence: 99%
See 2 more Smart Citations
“…Raj et al [ 21 ] reported that up to 40% of patients had excellent pain relief after a thoracic splanchnic nerve block, with only 15% of patients reporting poor results in a series of 107 patients with abdominal pain [ 21 ] . One study consisting of eight patients with chronic pancreatitis and two patients with chronic abdominal pain of an unknown etiology found that splanchnic radio-frequency ablation resulted in decreased pain scores, opiate usage, and hospital admissions for pain control [ 20 ] . Garcea et al [ 20 ] also found patients to have improvement in their level of anxiety, daily activity, mood, and overall perception of health.…”
Section: Splanchnicmentioning
confidence: 99%
“…One study consisting of eight patients with chronic pancreatitis and two patients with chronic abdominal pain of an unknown etiology found that splanchnic radio-frequency ablation resulted in decreased pain scores, opiate usage, and hospital admissions for pain control [ 20 ] . Garcea et al [ 20 ] also found patients to have improvement in their level of anxiety, daily activity, mood, and overall perception of health. One advantage of radio-frequency lesioning of splanchnic nerves is that the tissue that is damaged can be more precisely controlled, allowing the technique to be safer and perhaps more reliable than with the use of a neurolytic agent [ 21 ] .…”
Section: Splanchnicmentioning
confidence: 99%
See 1 more Smart Citation
“…At 18 months, pain scores, opiate analgesia use, and acute admissions for pain were reduced in conjunction with an improvement in mood, daily activity, and general perception of health. However, this has yet to be critically evaluated in controlled trials [27].…”
Section: Celiac Plexus Neurolysismentioning
confidence: 99%
“…Nerve plexus blocks are also effective for abdominal visceral pain 31 . Computer Tomography (CT) -guided neurolysis of the Coeliac plexus are very effective for the pain of pancreatitis, pancreatic cancer and other visceral pain including gastric, lower oesophageal and upper intestinal cancer.…”
Section: Choice Of Opioid For Spinal Infusionmentioning
confidence: 99%